The Influence of High Plasticity and Expansive Clay Stabilization with Limestone on Unconfined Compression Strength - Soewignjo Agus Nugroho; Gunawan Wibisono; Andarsin Ongko; Avrilly Zesthree Mauliza (Journal of the Civil Engineering Forum, 2021)
Clay is a cohesive material that becomes very soft when high content of water is added. This condition makes construction activities difficult on this type of soil. There is, therefore, a need for stabilization when dealing with high plasticity clay through several methods such as the application of limestone. However, this method mostly does not meet the standards due to the reaction between limestone and groundwater which normally alters soil properties, thereby, leading to a reduction in stickiness and softness of the soil. Meanwhile, limestone generally has the ability to compact and stabilize the soil due to its fine powder which consists of metals and non-organic mineral compositions. Therefore, this study was conducted to identify the influence of using limestone additives for stabilization at different mixture compositions on clay. The properties of the soil were tested before the Unconfined Compression Strength Test and the results showed limestone was effective in stabilizing high plasticity and expansive clay. This was proven by the 10% increase in the Unconfined Compression with lime content in curing conditions for 28 days as well as the 319% magnitude of the non-soaked, 6% reduction in the liquid limit value, and 46% increment in the plastic limit value.